Analysis Of The Impact Of Tumis Village On Poverty Levels In Sragen Regency - Dessy Purnama Sari; Muhammad Sabandi (Buletin Ekonomika Pembangunan, 2025)
Poverty is a reflection of people's welfare. The extent of poverty in a region is determined by the level of concern of the policymakers in that region, namely the Government. However, if poverty is left untreated, it will become a chronic disease that deepens economic and social disparities. Sragen Regency is recognised as the most innovative regency in Indonesia in the 2024 Innovative Government Award (IGA) program by the Ministry of Home Affairs for the Tumis Village (Tuntas Kemiskinan) innovation. This study aims to determine the impact of Tumis Village as a flagship program of the Sragen Regency Government in reducing poverty. This study is qualitative and uses descriptive methods. Data sourced from the Central Statistics Agency (BPS) of Sragen Regency and from interviews with residents affected by Tumis Village. The study results indicate that the Tumis Village program can reduce poverty in Sragen Regency. Keywords: Tumis Village, Poverty